Prevalence and Risk Factors for Eye Problems among 20-65 Years Old Iraqi Diabetics Patients - Kareem abed, Baqir; Abdul Rahim, Yousif; Abdul hameed Ali, May; Abbas, Muna F. (Journal of the Faculty of Medicine Baghdad, 2008)
Background: Diabetes is a chronic illness that requires continuing medical care to prevent acute complications and to reduce the risk of long-term complication. Eye diseases are the most feared complication of diabetes. The main disorders include diabetic retinopathy, cataracts and glaucoma. Early detection of these conditions is important to avoid risk of vision affection or even blindness. Objectives: This study aimed to assess the prevalence and risk factors for eye problems among 20-65 years old diabetics’ patients. Methods: We studied 2540 diabetic patients selected from the Specialized Center for Endocrinology & Diabetes and the National Center for Treatment & Research of Diabetes in Al-Mustanseria Collage of Medicine from the 1st of January, 2004 to the 31st of December, 2005. Structured questionnaires, full ophalmological examination were used to determine the prevalence of eye problems with their risk factors. Results: It was found that the prevalence of eye complications in the study sample was 45.4%, 30.2%, 14.6 and 3%, for reduction in visual acuity, retinopathy, cataract and glaucoma respectively. These ocular manifestations are common and cause a significant deterioration in the vision. Age, family history, duration of diabetic disease, smoking, and presence of chronic diseases (hypertension&ischemic heart disease), were found to be the main risk factors for the above complications which in turn lead to reduction in the visual acuity in diabetic patients. Conclusions: These ocular manifestations are common in diabetic patients and cause a significant deterioration in the vision. Regular ophthalmology, including slit-lamp examination, fundus examination and regular measurement of the intraocular pressure, are necessary for the early detection and management of potential complications.